The Application of Liquid Nitrogen Spray Cryotherapy in Treatment of Bronchial Stenosis. Issue 5 (September 2016) - Janke, Kelly J.; Abbas, Abbas El-Sayed; Ambur, Vishnu; Yu, Daohai
Abstract : Objective: Spray cryotherapy (SCT), the application of liquid nitrogen in a noncontact form, has been demonstrated to have efficacy in treating various types of pathologic lesions of the airway when used as an adjunct with bronchoscopy. The purpose of the study was to evaluate the results of the use of bronchoscopic SCT on the airway in a single institution. Methods: We performed a retrospective review of data collected on all patients who underwent SCT to re-establish or improve airway patency in an 11-month period. Patients were classified based on the nature of their disease into benign or malignant. Demographic data, change in luminal patency, and clinical outcomes were recorded. The percent of stenosis was divided into grades according to the following classification: 1, ⩽25%; 2, 26% to 50%; 3, 51% to 75%; and 4, ≥76%. We defined successful completion of treatment as obtaining a final patency of grade 1. Results: Twenty-two patients met inclusion criteria, with 45.5% (10 patients) having benign stenosis and 54.5% (12 patients) malignant. At initial bronchoscopic evaluation, the median grade of stenosis was 4 for malignant disease and 3.5 for benign disease. The median final posttreatment grade of stenosis was 2 for malignant disease and 1 for benign. The median improvement in grade of stenosis after treatment was 2 for both malignant and benign causes (Wilcoxon test, P = 0.92). Final patency of grade 1 was achieved in 42% of malignant stenosis and 80% of benign. Overall, 86.4% of patients had an improvement in grade of stenosis after treatment. The rate of morbidity was 4.5% (1/22) of all patients. Conclusions: The median change in grade after treatment was 2 grades of improvement for both the benign and malignant groups. These results provide evidence that the use of SCT is equally efficacious for both types of stenosis with an expectation of overall improvement in luminal patency, offering a safe and effective method of achieving airway patency in a minimally invasive fashion. This study contributes to the small but growing body of literature supporting the use of SCT in benign and malignant disease.